Posted by **dylan** on Sunday, April 21, 2013 at 8:35pm.

If cos^4 3 x - sin^4 3 x = cos (g(x)), then

g(x) = ??.

For part (b), use a^4-b^4=(a^2-b^2)(a^2+b^2)!

## Answer This Question

## Related Questions

- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- algebra - Can someone please help me do this problem? That would be great! ...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- tigonometry - expres the following as sums and differences of sines or cosines ...
- Trig - Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < ...
- Trig - Find sin(s+t) and (s-t) if cos(s)= 1/5 and sin(t) = 3/5 and s and t are ...
- Math(Please check) - Use the fundamental identities to simplify the expression. ...
- Precalc - Let x, y, and z be real numbers such that cos(x) + cos(y) + cos(z) = ...
- pre-cal - Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos ...

More Related Questions